Finite element modeling of impact shear resistance of double skin composite wall. (October 2016) - Hossain, Khandaker M.A.; Rafiei, Shahryar; Lachemi, Mohamed; Behdinan, Kamran; Anwar, Muhammed S.
Abstract: This paper presents the finite element (FE) modeling of a new form of composite walling system consisting of two skins of profiled steel sheeting and an infill of concrete subjected to in-plane impact loading. Composite wall specimen tested under impact shear loading in two phases, namely Phase I and Phase II was used to develop the FE model. In Phase I, the impact test was performed repeatedly keeping the impact energy of the projectile low intentionally to capture dynamic characteristics of the wall. In Phase II, the impact test was performed once with high impact energy (using maximum projectile speed the apparatus could produce). The developed FE model was used to simulate acceleration/displacement at the top of the wall during impact, impact energy dissipation, fundamental period, stress-strain development/concentration, shear strain/rate evolution, impact duration and bounce back impact time. The FE model predicted values/responses were found to be in good agreement with those obtained from experiments. Extensive parametric studies were conducted to study the influence of varying geometric, material and sheet-concrete interface parameters governing the composite wall performance under impact loading using the developed FE model. Highlights: Novel form of thin walled composite wall with profiled steel sheeting and concrete. Impact shear resistance of walls – with experimentation and modeling. Finite element modeling to simulate response such as acceleration, displacement and buckling. Parametric studies to study the influence of materials, geometric and connection parameters.